Internalisasi Nilai Tasamuh dalam Pembelajaran Pendidikan Agama Islam di Tingkat Sekolah Menengah Atas - Nuril Muttaqin; Hasniida Pokjiseng (Chalim Journal of Teaching and Learning, 2026)
This study aims to examine the process of internalizing tasamuh values in Islamic Religious Education learning at SMA Negeri 1 Dawarblandong Mojokerto. This research employed a qualitative case study approach. Data were collected through interviews, classroom observations, and documentation involving Islamic Religious Education teachers, school administrators, and students. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation of sources, methods, and time. The findings show that the internalization of tasamuh values occurs through three interconnected stages: planning, implementation, and behavioral implications. Teachers integrate tolerance values into lesson plans, apply dialogical learning, role modeling, and collaborative activities, which encourage students to practice tolerance in social interactions. As a result, students demonstrate respect for religious diversity, harmonious relationships with peers, and socially responsible behavior. These findings indicate that Islamic Religious Education plays a strategic role in strengthening tolerance and promoting social harmony in multicultural societies.